Knowledge, perceptions and practices regarding aflatoxins and aflatoxin management solutions among women: a perspective from two communities in Nigeria - Falade, T.D.O.; Kadjo, D.; Ortega-Beltran, A.; Atser, G.; Sanni, L. (Informa UK Limited, 2025)
Aflatoxins are hepatotoxins that can cause liver cancer, suppress immunity and impede normal development in children as antinutritional compounds. Women play significant roles in post-harvest activities and food preparation for their families. Therefore, awareness of aflatoxins and their mitigation across different demographic groups is important. Aflatoxin awareness studies in Kudan, Lere (Kaduna State), Kibiya and Doguwa (Kano State) local government areas (LGAs), Nigeria, were conducted to assess women’s level of knowledge of aflatoxins and aflatoxin management practices, including the use of Aflasafe® as pre-harvest for biological control of aflatoxins and the use of hermetic Purdue Improved Crop Storage (PICS) bags for post-harvest control. The awareness levels of aflatoxins and aflatoxin management practices among women were low, ranging from 0% to 26%. Women reported the re-introduction of rinsed discolored and insect-damaged grains for meal preparation. Meals prepared for weaning children, lactating mothers the convalescing and elderly frequently include maize. Grain samples provided by the women were analyzed, and 82% of the samples contained aflatoxin above 4 ppb, which is the regulatory limit for Nigeria. Food safety along the value chain from production to consumption is critical, and it is important to strategically include women during sensitization efforts, because of their importance in food handling and preparation.